2021
DOI: 10.3390/molecules26040863
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of a Polymethylmethacrylate Surface by Extended Anionic Surfactants: Effect of Branched Chains

Abstract: The adsorption behaviors of extended anionic surfactants linear sodium dodecyl(polyoxyisopropene)4 sulfate (L-C12PO4S), branched sodium dodecyl(polyoxyisopropene)4 sulfate (G-C12PO4S), and branched sodium hexadecyl(polyoxyisopropene)4 sulfate (G-C16PO4S) on polymethylmethacrylate (PMMA) surface have been studied. The effect of branched alkyl chain on the wettability of the PMMA surface has been explored. To obtain the adsorption parameters such as the adhesional tension and PMMA-solution interfacial tension, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Ge [ 16 ] studied the IFT of sulfate-based extended surfactant (NPP 3 S) and different weak base compound systems, and found that it has a good synergistic effect with Na 2 CO 3 in reducing the oil-water IFT. Jiang [ 17 ] explored the wettability of anionic nonionic surfactants on polymethyl methacrylate and investigated the influence of alkyl branching on the adsorption behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Ge [ 16 ] studied the IFT of sulfate-based extended surfactant (NPP 3 S) and different weak base compound systems, and found that it has a good synergistic effect with Na 2 CO 3 in reducing the oil-water IFT. Jiang [ 17 ] explored the wettability of anionic nonionic surfactants on polymethyl methacrylate and investigated the influence of alkyl branching on the adsorption behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The wetting phenomenon on solid surfaces has received considerable attention in a variety of fields such as adhesion, oil extraction, flotation, membrane distillation, washing and lubrication. [1][2][3][4][5] Surfactants play a crucial role in regulating the wetting properties of solid surfaces. Researchers have been continuously innovating the structure of surfactants to achieve better wetting performance.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have been continuously innovating the structure of surfactants to achieve better wetting performance. Over time, surfactants have evolved from single-chain to various special structures including alkylbranched double-zwitterionic head Gemini surfactants, 6,7 double-chained surfactants with dual hydrophobic chains, 8 inserted functionalized monomeric units, 4 amphoteric ions, 9 and alkyl-branched structures. 4 Among these, Gemini and double-chained surfactants have recently garnered much focus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with linear surfactants, branched surfactants exhibit preferable wetting ability toward potential application, which was mainly caused by the difference in diffusion rate. [18][19][20] Although high-branched alkyl tails may lead to poor biodegradability, branched surfactants with limited short side-chains have been testied to have negligible effect on their biodegradability. 21 With respect to the linear isomer, a branched alkyl amine oxide surfactant (C 10 DAO-branched) showed the ability to form concentrated solutions without generating lyotropic liquid crystals 22 or to tune supramolecular aggregation upon pH stimuli.…”
Section: Introductionmentioning
confidence: 99%